Strengthening Organizational Culture through Total Quality Management: A Moderated Model of Transformational Leadership - Herlina Tri Wulandari; H Harsono; I Indri (Universitas Muhammadiyah Surakarta, 2025)
This study has a purpose to analyze the influence of the application ofTotal Quality Management (TQM) in strengthening organizational culture in vocational education, with transformational leadership as a mod-erating variable. This study was motivated by the challenges faced by SMK Negeri 4 Klaten in developing a culture of caring, contributing, and collaborating to improve school performance and graduate readiness. Employing a quantitative cross-sectional design, data were accumulated from 307 respondents consisting of teachers, staff, and students through a structured questionnaire that measured Total Quality Manage-ment (TQM), organizational culture, also transformational leadership. Structural Equation Modeling (SEM) with AMOS was utilized to appraise the direct and moderating effects, preceded by validity and reliability testing utilizing Confirmatory Factor Analysis, Composite Reliability, also Average Variance Extracted. The results showed that the application of Total Quality Management (TQM) significantly and positively influ-enced organizational culture, and transformational leadership also unfolded a significant positive effect. Furthermore, transformational leadership strengthened the relationship between Total Quality Management (TQM) and organizational culture, confirming its moderating role in internalizing quality values throughout the school environment. This study adds to the treatise on quality management in education by integrating Total Quality Management (TQM) and transformational leadership in the realm of vocational schools. Practically, the findings offer recommendations for school leaders to enhance quality improvement efforts by strengthening leadership capacity and instilling a culture of caring, contribution, and collaboration. These concepts are valuable for policymakers in designing quality assurance strategies that combine managerial systems with leadership-driven cultural development.